Labor and the Market Value of the Firm - Merz, Monika; Yashiv, Eran (American Economic Review, 2007)
What role does labor play in firms' market value? We use a production-based asset pricing model with factor adjustment costs and forward-looking agents to explore this question. We posit that the hiring of labor is akin to investment in capital and that the two interact, with the interaction being a crucial determinant of the dynamic behavior of market value. Using aggregate US corporate sector data, we estimate firms' optimal hiring and investment decisions and the consequences for firms' value. (JEL E22, E24, G31, G32, M51)